2012
DOI: 10.5588/pha.12.0044
|View full text |Cite
|
Sign up to set email alerts
|

A nested case-control study on relapse predictors among tuberculosis patients treated in Yemen's NTCP

Abstract: high relative relapse rate (RRR) of 6-11% between 1995 and 2009, exceeding the acceptable norm (<5%). [3][4][5] The present study was designed to measure the actual relapse rate and to identify associated risk factors. METHODS Study designA prospective nested case-control study was conducted to identify risk factors for relapse among TB patients. At the end of the follow-up period (28 February 2010), all those who relapsed within 12 months after completion of treatment were identifi ed from the tuberculosis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“… 10 – 68 A total of 17 studies were case–control studies comparing DM/TB to non-DM/TB patients. 16 , 19 , 25 , 28 , 30 , 36 , 37 , 42 , 44 , 47 51 , 54 , 55 , 65 Five studies were cross-sectional, 14 , 20 , 29 , 33 , 52 one was prospective, 10 and the remainder were retrospective studies evaluating the demographic and clinical characteristics of TB-infected patients. Iran contributed the most studies (16 studies) and the fewest were from Yemen and Oman (one each).…”
Section: Resultsmentioning
confidence: 99%
“… 10 – 68 A total of 17 studies were case–control studies comparing DM/TB to non-DM/TB patients. 16 , 19 , 25 , 28 , 30 , 36 , 37 , 42 , 44 , 47 51 , 54 , 55 , 65 Five studies were cross-sectional, 14 , 20 , 29 , 33 , 52 one was prospective, 10 and the remainder were retrospective studies evaluating the demographic and clinical characteristics of TB-infected patients. Iran contributed the most studies (16 studies) and the fewest were from Yemen and Oman (one each).…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate logistic regression showed that smoking and the existence of cavity and diabetes were associated with recurrence but age and sex had no significant relation. [ 19 ] In a study conducted in India, 458 pulmonary TB patients were studied in 2012. It was reported that 66 (14.5%) patients had diabetes and the recurrence rate in diabetic patients were more than in those without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have similarly reported a strong association between general comorbid conditions and high defaulter rate . A study performed in Yemen indicated that diabetic comorbidity is highly associated with relapse, and suggested the screening of TB patients with comorbid conditions …”
Section: Discussionmentioning
confidence: 90%
“…[59] A study performed in Yemen indicated that diabetic comorbidity is highly associated with relapse, and suggested the screening of TB patients with comorbid conditions. [60] In addition, side effects during treatment was proven to be a risk factor of defaulting from treatment. Approximately, 32.7% of the patients reported side effects as their main reason for defaulting.…”
Section: Risk Factors Associated With Tuberculosis Defaultersmentioning
confidence: 99%